Iot based supply chain management - Alam, Ajmain Inqiad; Rahman, Mahfuzur; Subho, Md. Razaul Haque (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.